A review of three major sociological theories and an Islamic perspective - Hayatullah Laluddin, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
This article examines critically the three major sociological theories namely, Structural Functionalism, Symbolic Interactionism and Conflict theory. These theories are formulated on the pattern of science where scientific method is strictly adhered to. Considering the nature and the essence of the social phenomenon and its component parts the author argues that the application of pure scientific method in the study or analysis of the social phenomenon fail to present an accurate understanding of the social phenomenon. Thus, an alternative method which is capable of taking into consideration both physical and metaphysical aspects of the social phenomenon is required. Toward this end this article attempts to delineate the three major theories of sociology, their shortcoming and loophole, then attempt to highlight the constituent elements of the social phenomenon and their significance in formulation of comprehensive sociological theories. An Islamic perspective on sociological theories is also provided in the last part of this article where the discrepancy of the sociological theories are disclosed and a proposal for a more dynamic method for the formulation of sociological theories of comprehensive nature is made.